The effect of humidity and temperature on visual outcomes after myopic corneal laser refractive surgery - Hood, Christopher; Shtein, Roni; Veldheer, Daniel; Hussain, Munira; Niziol, Leslie; Musch, David; Mian, Shahzad (Clinical ophthalmology (Auckland, N.Z.), 2016)
To determine whether procedure room environmental conditions are associated with outcomes after myopic laser in situ keratomileusis (LASIK) or laser-assisted keratomileusis (LASEK). Retrospective chart review. Eight hundred sixty-three eyes of 458 consecutive patients at a university-based academic practice. We reviewed the medical records of consecutive patients who underwent LASIK or LASEK over a 3-year period. Linear mixed regression models were used to investigate the association of laser room temperature and humidity with the outcomes of visual acuity and postoperative manifest spherical equivalent refraction. Repeated measures logistic regression models were used for the outcomes of diffuse lamellar keratitis (DLK) and need for enhancement surgery. Subjects were on an average 38.6 years old at the time of surgery (standard deviation [SD] =10.3) and the average spherical equivalent refraction of eyes was 3.8 diopters (SD =2.03). Regression models did not reveal a significant association between temperature and uncorrected distance visual acuity (UDVA) or corrected distance visual acuity (CDVA), or between humidity and UDVA ( >0.05 for all). However, increased humidity was associated with a small but statistically significant improvement in CDVA after LASIK at 1 day, 1 month, 3 months, and 1 year postoperatively ( <0.05 for all). There was no significant association between temperature and humidity and the need for enhancement, the incidence of DLK, or postoperative manifest refraction. While increased laser room humidity was consistently associated with small improvements in CDVA after myopic LASIK over time, variations in room temperature and humidity were not associated with UDVA, the need for enhancement, the incidence of DLK, or refraction after myopic LASIK or LASEK.